Trends in delivery mode occurring during the Covid-19 pandemic and risks in long-term urogynecology cases: A narrative review - Eighty Mardiyan Kurniawati; Gatut Hardianto; Hari Paraton; Azami Denas Azinar; Tri Hastono Setyo Hadi; Nur Anisah Rahmawati (Majalah Obstetri dan Ginekologi, 2021)
HIGHLIGHT 1. Trend of delivery types during Covid-19 pandemic and the risk of urogynecology cases, particularly sexual dysfunction, pelvic floor dysfunction and stress urinary incontinence, was reviewed.2. Cesarean section was found higher than normal deliveries due to the consideration of possiblee exposure to the virus.3. Sexual dysfunction was found not to have relations to mode of delivery, but those with mode of delivery other than normal likely had dyspareunia at 18 months postpartum.4. The choice of method of delivery needs to be determined wisely by considering medical indications and the risk factors. ABSTRACTWomen's quality of life in the long term is also influenced by their reproductive health. Various diseases appear related to urogynecology cases such as sexual dysfunction, pelvic floor dysfunction and stress urinary incontinence. The study reviews the trend of types of delivery during the pandemic and the risk of urogynecology cases, especially in the three cases. The narrative review study was conducted using the PubMed, Science Direct, and Google Scholar databases. The results showed that the percentage of cesarean section was higher than normal deliveries because of the view on the safety of exposure to the virus. Several studies have found that sexual dysfunction was not related to mode of delivery but women who delivered by emergency caesarean section, vacuum extraction, or caesarean section were more likely to report dyspareunia at 18 months postpartum but adjusted for maternal age and other confounders. Meanwhile, compared with spontaneous vaginal delivery, cesarean delivery with a protective effect or reduction of stress urinary incontinence, overactive bladder, and pelvic organ prolapse. There is a tendency to choose a certain pattern of delivery so that the choice of method needs to be chosen wisely and through medical indications and consider risk factors for long-term reproductive health problems.